How could a new universal code of conduct prevent and resolve sovereign debt crises? Proposals for design and implementation - Kathrin Berensmann (Journal of Economic Surveys, 2022)
In response to the COVID-19 crisis, government spending around the world has increased significantly and will continue to grow as interest rates rise. In view of protracted and costly sovereign debt restructurings in the previous decades, contractual and noncontractual instruments of the Global Debt Governance-system have been insufficient to prevent and to resolve sovereign debt crisis. While statutory and comprehensive approaches to resolve sovereign debt crises lack the political support such as an insolvency procedure for states incomprehensive contractual approaches including collective action clauses (CACs) cannot fully secure a comprehensive debt resolution. Codes of conduct could constitute an essential instrument to contribute to preventing and resolving sovereign debt crises. There are two main impediments for establishing and adopting such codes of conduct effectively. First, a range of codes of conduct with different institutional settings and principles have been established - and partly implemented - including those of the Institute of International Finance, the United Nations, the G20, the IMF and the OECD. However, differing institutional settings do not contribute to preventing or effectively resolving debt crises when the actors concerned apply different codes of conduct. We suggest a new universal code of conduct in which the elements of the various proposals made by the public and private sectors would be combined. Second, the global economic governance structure lacks incentives for creditors and debtors to adhere to this new universal code of conduct. This paper proposes measures providing incentives for creditors and debtors to apply the nonstatutory code of conduct.
Keywords: 330; code of conduct; collective action clauses; COVID-19; debt crisis; debt; sovereign debt